Distraction Osteogenesis in Management of Mandibular Deformities - Menon, Suresh (Med J Armed Forces India, 2005)
BACKGROUND: The concept of Distraction Osteogenesis is applied in Maxillofacial surgery extensively in the recent past, revolutionizing the concept of management of facial deformities specially the mandible. METHODS: This article describes intra oral mandibular distractors in managing mandibular deformities in 9 cases. CONCLUSION: Surgical intervention is possible in very young patients. Distraction Osteogenosis does not reduce the need for orthodontic intervention. A multifarious approach to the problem, should form the basis of treatment of mandibular deformities.